Genome Sequence of Klebsiella pneumoniae Respiratory Isolate IA565 - Johnson, Jeremiah G. (American Society for Microbiology, 2014)
Klebsiella pneumoniae is a clinically significant opportunistic bacterial pathogen as well as a normal member of the human microbiota. K. pneumoniae strain IA565 was isolated from a tracheal aspirate at the University of Iowa Hospitals and Clinics. Here, we present the genome sequence of K. pneumoniae IA565.